Kinerja Guru Ditinjau dari Kepemimpinan Kepala Sekolah dan Faktor Kontekstual di SMA Negeri 1 Teras Boyolali Tahun 2016 - Aji, Bambang Wasito; , Drs. Muhammad Yahya, M.Si; , Dra. Titik Asmawati, SE, M.Si (2016)
Bambang Wasito Aji, A210120068. Teacher performance in terms of Leadership Principal and Contextual Factors in SMA Negeri 1 Teras Boyolali Year 2016. Study Program of Accounting Education, the Faculty of Education, Muhammadiyah University of Surakarta, August 2016 This study aims to determine: 1) The impact of school leadership on teacher performance, 2) Influence of contextual factors on teacher performance, 3) The impact of school leadership and contextual factors on teacher performance. This study is quantitative descriptive research by drawing conclusions through statistical methods. This study included a population study by respondents as many as 55 teachers. The instrument used in this study was a questionnaire and documentation. Questionnaire previously trialed and tested for validity and reliability test. Data analysis technique used is multiple linear regression analysis, t-test, F, coefficient determination (R ²) and partial coefficient of determination (r²). The results of the regression analysis obtained regression equation: Y = 26.140 + 0,853X1 + 1,659X2. The equation shows that the performance of teachers affected by school leadership and contextual factors. The conclusions drawn are: 1) Leadership principals positive influence on teacher performance. It is based on regression analysis (t test) note that tcount > ttable is 3,307> 2,004 and the significance value < 0.05 is 0,025 with partial determination coefficient of 17.88%. 2) contextual factors positive influence on teacher performance. It is based on regression analysis (t test) note that tcount > ttable namely 3.509> 2.004 and the significance value < 0.05 is 0.001 with a partial determination coefficient of 29.81%. 3) Leadership principals and contextual factors positive influence on teacher performance. This is based on multiple regression analysis of variance (F test) note that Fcount > Ftable is 23.728 > 3.16 and a significance value < 0.05 is 0.000. 4) The coefficient of determination (R2) of 0.477 indicates that the influence of school leadership and contextual factors on the performance of teachers is 47.7%, while the rest influenced by other variables. Keywords: contextual factors, leadership principal, teacher performance.